Ab initio and CALPHAD-type thermodynamic investigation of the Ti–Al–Zr system (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
Ti–Al based alloys have been widely used in the aeronautics and aerospace. Adding alloying element Zr can significantly improve their high-temperature endurance and corrosion resistance. To investigate the influence of the addition of element Zr on the properties of the Ti–Al system, ab initio calculations and the CALPHAD (CALculation of PHAse Diagrams) method were used to evaluate the Ti–Al–Zr ternary system. Ab initio calculations were employed to obtain the formation enthalpies of intermetallic compounds. CALPHAD approach was used to optimize the thermodynamic parameters based on experiments. The experimental data of phase equilibria at 1073, 1273, 1473, and 1573 K, as well as a vertical section of the Ti3Al–Ti + 5 wt.% Zr were used to assess this system. The thermodynamic parameters of the binary Ti–Al, Al–Zr and Ti–Zr systems were acquired from recent assessments, and the ternary ones were evaluated in this work. The Ti–Al–Zr ternary dataset has been established and the calculated results are in close agreement with the experimental data on both thermodynamics and phase equilibria.